Case report: A novel de novo IGF2 missense variant in a Finnish patient with Silver-Russell syndrome - Loid, Petra; Lipsanen-Nyman, Marita; Ala-Mello, Sirpa; Hannula-Jouppi, Katariina; Kere, Juha; Mäkitie, Outi; Muurinen, Mari (Frontiers in Pediatrics, 2022)
Silver-Russell syndrome (SRS, OMIM 180860) is a rare imprinting disorder characterized by intrauterine and postnatal growth restriction, feeding difficulties in early childhood, characteristic facial features, and body asymmetry. The molecular cause most commonly relates to hypomethylation of the imprinted 11p15.5 IGF2/H19 domain but remains unknown in about 40% the patients. Recently, heterozygous paternally inherited pathogenic variants in IGF2, the gene encoding insulin-like growth factor 2 (IGF2), have been identified in patients with SRS. We report a novel de novo missense variant in IGF2 (c.122T>G, p.Leu41Arg) on the paternally derived allele in a 16-year-old boy with a clinical diagnosis of SRS. The missense variant was identified by targeted exome sequencing and predicted pathogenic by multiple in silico tools. It affects a highly conserved residue on a domain that is important for binding of other molecules. Our finding expands the spectrum of disease-causing variants in IGF2. Targeted exome sequencing is a useful diagnostic tool in patients with negative results of common diagnostic tests for SRS.